1/7 = 3/4x-1
3/4x=1/7+1=8/7
x=8/7*4/3=32/21
4x - 2y = 14
y = 0.5x -1
Get just one variable on one side for both equations.
4x - 2y = 14 ⇒ 4x = 2y + 14 ⇒ 4x - 14 = 2y
y = 0.5x - 1 ⇒ x - 2 = 2y
Use the transitive property and then solve for x.
x-2 = 4x-14
12 = 3x
x = 4
<em>Edit: Apprently I didn't use substitution. Oops! Sorry...</em>
Answer:
ab = 2
Step-by-step explanation:
Given equations
ax² +ax + 2 = 0
x² + x + b = 0
root of both the equation
x= 1
then we can plug in x = 1 in both the equation
ax² +ax + 2 = 0 x² + x + b = 0
a*1² +a*1 + 2 = 0 1² + 1 + b = 0
a +a + 2 = 0 1 + 1 + b = 0
2a + 2 = 0 2 + b = 0
2a = - 2 b = -2
a = -2/2 = -1
Thus,
a = -1
b = -2
a*b = -1*-2 = 2
ab = 2
4(4x + 5)
4(4•7+5)
4(28+5)
4(33)
132